Mass clonal propagation of selected bamboo genotype for construction purposes in Malaysia - Lee, Pay Chiann (2020)
Malaysia is one of the leading exporters of tropical timber products in the world, to fulfil the market demand for construction materials as world population is expected to reach 9.7 billion in year 2050, natural forest stand will not be sufficient. Forest plantation development programme established in 2005, and bamboo has been recommended as one of the species to produce timber quality material. In 2018, the global export of bamboo-based products amounted at RM 287.2 billion and Malaysia was able to export RM 9.97 million worth of bamboo and bamboo products. The timber species and sufficient stock of planting material has always been the biggest concern to produce quality timber for forest plantation. Thus, to mitigate these issues, identifying potential species such as bamboo and technology to mass produce these identified genotypes must be assessed. The objectives of the current research were to evaluate the physical and mechanical properties as well as to develop a suitable in vitro protocol for mass clonal propagation of Bambusa vulgaris ‘Striata’, Bambusa vulgaris and Dendrocalamus asper. Three matured culms of bamboo were sampled randomly from two selected clumps each, further divided into three equal lengths of 3 m each marked as bottom, middle and top. Samples were taken from nodal and internodal parts from each levels of height for properties evaluation. Physical properties included moisture content, density and shrinkages while three-point bending test was used to evaluate flexural modulus and flexural strength. The properties were all significantly different between species at p ≤ 0.05, except the modulus of elasticity (MOE) were non-significant. The highest moisture content was observed in B. vulgaris ‘Striata’ (55.28 %) and the lowest in D. asper (33.13 %). For both B. vulgaris ‘Striata’ and B. vulgaris, moisture content was the highest at the top level (56.32-58.08 %), and also at internodal section (54.60-57.66 %). D. asper has highest moisture content at the bottom level (38.71 %) and nodal section (34.53 %). Density was the highest in D. asper (0.93 g/cm3), the lowest in B. vulgaris ‘Striata’ (0.70 g/cm3). Higher density was observed at bottom and middle level for B. vulgaris ‘Striata’ (0.69-0.73 g/cm3) and B. vulgaris (0.77-0.83 g/cm3), while highest density was observed at top level in D. asper (0.94-0.97 g/cm3). Node had higher density in B. vulgaris ‘Striata’ (0.71-0.74 g/cm3) and D. asper (0.92-0.94 g/cm3), while B. vulgaris had the same density for node and internode (0.74-0.82 g/cm3). Tangential shrinkage of bamboo strips was recorded the highest in B. vulgaris ‘Striata’ (23.52 %) and the lowest in D. asper (1.45 %). Highest shrinkage was observed at middle and top levels for B. vulgaris ‘Striata’ (25.33-26.29 %) and B. vulgaris (16.45-19.44 %), at bottom level for D. asper (1.40-2.66 %). Node shrunk greater in B. vulgaris ‘Striata’ (32.01-32.48 %) and internode shrunk greater in D. asper (1.52-2.30 %). The highest MOE was observed in D. asper (12,262 MPa), and the lowest in B. vulgaris ‘Striata’ (11,890 MPa). Highest MOE was observed at top level in B. vulgaris (12,968-13,841 MPa) and D. asper (14,276-14,519 MPa). Internode had higher MOE in D. asper (13,785-14,595 MPa) and B. vulgaris (97-106 MPa), while node had higher MOE in B. vulgaris ‘Striata’ (106-124 MPa). The highest modulus of rupture (MOR) was observed in D. asper (119 MPa) and the lowest in B. vulgaris (97 MPa). Highest MOR obtained from bottom level of B. vulgaris (99-113 MPa), bottom and middle in B. vulgaris ‘Striata’ (115-116 MPa), top level for D. asper (134-140 MPa). Internode sections had higher MOR than node for both B. vulgaris (97- 106 MPa) and D. asper (147-161 MPa), while B. vulgaris ‘Striata’ was on the contrary (106-124 MPa). Both B. vulgaris and B. vulgaris ‘Striata’ have showed as reliable resources to be considered as potential plantation species like D. asper. Nodal segments (2.5-3.0 cm) from lateral branches were collected as explant for in vitro propagation. The explants pre-sterilized in Benomyl (0.1 %), Streptomycin (0.2 %), Boric acid (1.0 %) for 60 minutes had significantly reduced the percentage of microbial contamination, 15-20 % of aseptic culture was able to produced. In surface sterilization, 0.1 % of mercuric chloride (HgCl2) was observed to be the best compound to produce clean and viable cultures. The exposure time of 10, 8, and 5 minutes were obtained as the best to produce highest percentage of aseptic culture for B. vulgaris ‘Striata’ (73 %), B. vulgaris (67 %) and D. asper (85 %) respectively. The explants were then inoculated into MS media supplemented with 6-Benzylaminopurine (BAP). BAP (0, 1, 2, 3, 4, 5, 10 mg/L) were tested for B. vulgaris ‘Striata’ and B. vulgaris, and BAP (0, 1, 3, 5, 10, 15, 20 mg/L) were tested for D. asper. MS media supplemented with 5 mg/L of BAP was optimum for B. vulgaris ‘Striata’ and D. asper while 3 mg/L was optimum for B. vulgaris in bud breaking stage. 50 % of bud breaking was achieved in B. vulgaris ‘Striata’ with mean number of shoots of 1.8 and mean length of 3.01 cm. For B. vulgaris, 65 % of bud break with 1.23 shoots of 4.08 cm were produced. 70 % of bud break with 1.74 shoots of 1.37 cm length of shoots were recorded for D. asper. The protocol for in vitro propagation achieved for bud breaking is effective and further development are needed for future tests.